2017
DOI: 10.3201/eid2301.161497
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Infections with Multidrug-Resistant Yeast Candida auris, Colombia

Abstract: Candida auris is an emerging multidrug-resistant fungus that causes a wide range of symptoms. We report finding 17 cases of C. auris infection that were originally misclassified but correctly identified 27.5 days later on average. Patients with a delayed diagnosis of C. auris had a 30-day mortality rate of 35.2%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
166
2
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(196 citation statements)
references
References 7 publications
14
166
2
14
Order By: Relevance
“…After observing the unusual prevalence and the micromorphological discordance, the strains were cultured in CHROMagar Candida medium using MALDI-TOF. Pink colonies were observed in the CHROMagar Candida medium and there was subsequently molecular confirmation of C. auris in all isolates 14 . According to Chowdhary et al, growth at 40 °C may differentiate the isolates of C. auris that are mistakenly identified as C. haemulonii by VITEK, considering that the species Candida haemulonii does not grow at 40 °C.…”
Section: Identificationmentioning
confidence: 97%
See 4 more Smart Citations
“…After observing the unusual prevalence and the micromorphological discordance, the strains were cultured in CHROMagar Candida medium using MALDI-TOF. Pink colonies were observed in the CHROMagar Candida medium and there was subsequently molecular confirmation of C. auris in all isolates 14 . According to Chowdhary et al, growth at 40 °C may differentiate the isolates of C. auris that are mistakenly identified as C. haemulonii by VITEK, considering that the species Candida haemulonii does not grow at 40 °C.…”
Section: Identificationmentioning
confidence: 97%
“…guilliermondii, S. cerevisiae and R. glutinis and that presented high minimal inhibitory concentrations (MIC) for fluconazole (FCZ; MIC≥ 32 µg/mL), voriconazole (VCZ; MIC≥ 2 µg/mL), amphotericin B (APHB; MIC≥2 µg/mL), and echinocandins (ECHs), such as anidulafungin (ADA; ≥2 µg/mL) 9 . This new species can be erroneously identified as those mentioned above 9,14 , if identification is made through classical methods 6,9 . Gaitan et al 6 initially described isolates identified as S. cerevisiae, C. sake, C. lusitaniae, C. haemulonii, and eight inconclusive isolates, and 8 (eight) were isolated from the blood and 4 (four) from the tip of the catheter, from patients hospitalized in an ICU in a European hospital.…”
Section: Identificationmentioning
confidence: 97%
See 3 more Smart Citations